Training in Making Interactive Learning Media (Cycle of Hydrology and Layers of the Atmosphere) SMAN 5 Pariaman and SMAN 1 Ulakan Tapakis, Padang Pariaman - Chandra, Deded; Mariya, Sri; Nova, Sari; Edial, Helfia; Rahmi, Lailatur; Putri, Srikandi; Novio, Rery; Nofrion, Nofrion; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
The aims of this article are to improve the ability of teachers and students to create interactive learning media and improve the understanding and ability of teachers in pedagogic aspects that can be seen from the process of designing a Lesson Plan (RPP), especially in terms of choosing a model or method and learning media. . This activity was carried out at SMAN 5 Pariaman and at SMAN 1 Ulakan Tapakis, Padang Pariaman using training methods, question and answer and practice. The participants involved are geography teachers and students who are represented in each class with 5 participants. With the Covid-19 Pandemic and the appeal from the government to comply with health protocols by checking temperature, washing hands, using hand sanitizers, maintaining distance, and wearing masks, this activity is carried out with limited participants, so that Covid-19 does not become the newest cluster in the region. activity. These activities include conducting training related to the design of effective learning media and conducting training related to the manufacture of interactive learning media for the cycle of hydrology and layers of the atmosphere for geography teachers and students. The results of the training at SMAN 5 Pariaman and at SMAN 1 Ulakan Tapakis, Padang Pariaman, were in the form of 3D media and increased the abilities possessed by teachers and students in making learning media, in this case, the 3D media of the cycle of hydrology and layers of the atmosphere. From this training, teachers get an increase in their ability to understand pedagogical aspects which can be seen from the process of designing lesson plans, especially in terms of choosing models and learning media. Geography teachers also better understand adequate competence in terms of designing and utilizing media so as to create quality, effective and interactive learning.